2022
DOI: 10.3390/microorganisms10050967
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of S1RBD-Specific IgG Antibody Responses following COVID-19 Vaccination in Healthcare Professionals in Cyprus: A Comparative Look between the Vaccines of Pfizer-BioNTech and AstraZeneca

Abstract: There is an ongoing effort to report data on SARS-CoV-2 antibodies in different individuals. Ninety-seven healthcare workers were enrolled in this study (Pfizer’s BNT162b2, n = 52; and AstraZeneca’s ChAdOx1-S, n = 45) and S1RBD-specific IgG antibodies were analyzed over time. Both vaccines induced S1RBD-specific antibodies after the second dose. A significant increase in S1RBD-specific IgG median levels 3 weeks following the second dose was detected (BNT162b2, 118.0 BAU/mL to 2018.0 BAU/mL; ChAdOx1-S, 38.1 BAU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
0
0
Order By: Relevance
“…In contrast, three months after the two homologous vaccine doses the antibody levels waned more rapidly in the BNT162b2 recipients when compared to the ChAdOx1 vaccinated individuals. Similar trends were observed among the HCWs vaccinated with the BNT126b2 or ChAdOx1 vaccine in Cyprus [18]. Our results are also in line with a large-population-based analysis by Wei et al, who demonstrated that following the homologous BNT162b2 vaccination anti-SARS-CoV-2 S IgG antibodies titres were higher but waned faster over time in comparison to vector vaccination [19,20].…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, three months after the two homologous vaccine doses the antibody levels waned more rapidly in the BNT162b2 recipients when compared to the ChAdOx1 vaccinated individuals. Similar trends were observed among the HCWs vaccinated with the BNT126b2 or ChAdOx1 vaccine in Cyprus [18]. Our results are also in line with a large-population-based analysis by Wei et al, who demonstrated that following the homologous BNT162b2 vaccination anti-SARS-CoV-2 S IgG antibodies titres were higher but waned faster over time in comparison to vector vaccination [19,20].…”
Section: Discussionsupporting
confidence: 90%
“…From this summary, we extracted only IgG S1-RBD measures and excluded viral vector vaccine responses as those appeared to differ from mRNA and recombinant protein vaccine responses. This left five studies that provided a peak IgG S1-RBD range of 1372-2744 BAU/mL post-vaccination [22,27,28,30,31]. We observed that the peak IgG S1-RBD response measured in our healthcare worker cohort, 2266 BAU/mL (Figure 1), for infection-naive individuals at baseline, falls within this range.…”
Section: Sars-cov-2 Antibody Levels In Immunocompetent Individualsmentioning
confidence: 73%